Development of a Student Handling Book Based on AppSheet Platform for the Effectiveness of Responsive Services by Guidance and Counseling Teachers - Nuryadin, Cece Agus; Rusdiyani, Isti; Sholih, Sholih (Jurnal Dimensi Pendidikan dan Pembelajaran, 2025)
Innovation in education is always necessary in every era to meet the needs and developments of society. Guidance and counseling teachers are an important part that must continue to innovate, especially in providing services to students. However, with a limited number of teachers not proportional to the number of students, media or platforms are needed to assist teachers in providing responsive, effective, and efficient services. To address this challenge, the development of student-handling books based on the AppSheet platform is the right solution. AppSheet is an efficient and innovative platform in developing counseling services, especially responsive ones. This research uses the Research and Development (RD) method with the ADDIE model, focusing on the development of student handling books based on the Appsheet platform to improve the effectiveness of guidance and counseling teachers' responsive services. The development results show that the AppSheet platform is feasible and can be used based on validation tests by media experts scoring 88% and subject matter experts scoring 95%. Its effectiveness is also evidenced by the positive response from guidance and counseling teachers, reaching 86% in pre-test results and achieving 75% in post-test results, reflecting the effectiveness of the AppSheet platform in counseling service activities. Thus, the development of student handling books based on the AppSheet platform can be effectively used in responsive guidance and counseling services.